2011
DOI: 10.1186/gb-2011-12-10-r107
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of the carcinogenic human liver fluke Clonorchis sinensis

Abstract: BackgroundClonorchis sinensis is a carcinogenic human liver fluke that is widespread in Asian countries. Increasing infection rates of this neglected tropical disease are leading to negative economic and public health consequences in affected regions. Experimental and epidemiological studies have shown a strong association between the incidence of cholangiocarcinoma and the infection rate of C. sinensis. To aid research into this organism, we have sequenced its genome.ResultsWe combined de novo sequencing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 87 publications
(122 reference statements)
4
144
0
Order By: Relevance
“…The availability of entire genome sequences of related species of liver flukes, such as C. sinensis (89) and blood flukes (38 -40), now provides unprecedented opportunities to (i) conduct comparative proteomic comparisons; (ii) elucidate the structures and functions of key molecules (e.g. "endogenous" and "exogenous" cathepsins); (iii) explore novel biological pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of entire genome sequences of related species of liver flukes, such as C. sinensis (89) and blood flukes (38 -40), now provides unprecedented opportunities to (i) conduct comparative proteomic comparisons; (ii) elucidate the structures and functions of key molecules (e.g. "endogenous" and "exogenous" cathepsins); (iii) explore novel biological pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The recovered hidden orthologs have an immediate impact on our understanding of gene complement evolution in Platyhelminthes, particularly those lineages that are the subject of intense research, such as the regenerative model Schmidtea mediterranea and parasitic flatworms (Berriman et al 2009;Wang et al 2011;Olson et al 2012;. The identification of fast-evolving orthologs for important centrosomal proteins in S. mediterranea and other flatworms lineages (Fig.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…The use of more molecularly conserved flatworm lineages, such as P. vittatus, can improve the identification of candidate genes, as well as help with the annotation of the increasingly abundant flatworm RNA-seq and genomic data sets (Berriman et al 2009;Wang et al 2011;Tsai et al 2013;Robb et al 2015;Wasik et al 2015;Brandl et al 2016). Therefore, we have now made available an assembled version of those highly complete nonplanarian flatworm transcriptomes in PlanMine, an integrated web resource of transcriptomic data for planarian researchers (Brandl et al 2016).…”
Section: Uncovered Hidden Orthology In Flatwormsmentioning
confidence: 99%
“…This highlights the fact that there are physio-chemical differences in the channel for possible substrate recognition function and specificity of isoforms. This may partly explain the functional outcomes of inflammation, hepatic fibrosis and cancer caused by infection of the parasite, C. sinensis [5][6][7].…”
Section: Sequence Analysismentioning
confidence: 99%
“…Interestingly, the genome of the liver fluke revealed that there are genes missing for the production of its own fatty acids. This makes the bile as the only source of lipid for its growth [5]. The CsIIIPLA 2 is therefore an important energy source enzyme of the adult parasite.…”
Section: Introductionmentioning
confidence: 99%